Ultra-sensitive, stretchable, and bidirectional wearable strain sensor for human motion detection. Issue 18 (25th April 2022) - Yang, Chunqing; Zhang, Dongzhi; Wang, Dongyue; Chen, Xiaoya; Luan, Huixin
Abstract : This paper reviews the experimental setup and results of MXene/SnS2 /SA-based flexible strain sensors. Abstract : Flexible strain sensors are widely used in electronic skin, medical diagnosis, and human movement and health detection. It is urgent to prepare portable high-performance flexible sensors with excellent sensitivity, ultra-low detection limit, broad detection range and simple structure. In this work, the MXene/SnS2 /SA sensitive material was sprayed on a PDMS substrate and encapsulated on the top layer by PDMS. A bidirectional sandwich structured sensor with good stretchability (up to 70% strain), adjustable linear sensing range (0–60% strain), ultra-high sensitivity (a giant gauge factor as high as 7178), excellent repeatability and stability (>600 cycles), and quick response was successfully fabricated. The sensor also demonstrates a large pressure sensing range (0–350 kPa), high sensitivity (0.97 kPa −1 ), and fast response/recovery time (300 ms/200 ms). The sensor has superior application potential in detecting subtle health signals and large-scale motion signals. The device has a strong structure, excellent performance and stable detection output, and is expected to find application in wearable electronic devices.